Pengaruh Current Ratio, Debt To Equity Ratio, Dan Total Asset Turnover Terhadap Price Earning Ratio (Studi Kasus pada Perusahaan Subsektor Industri Makanan dan minuman yang Terdaftar di Bursa Efek Indonesia Periode 2011-2020) - Matsani, Matsani (JUDICIOUS, 2023)
This research aims to analyze the Influence of Current Ratio, Debt to Equity Ratio, and Total Asset Turnover on Price Earning Ratio. The population for this study consists of four food and beverage companies listed on the Indonesia Stock Exchange during the period from 2011 to 2020. The sample used in this research is a saturated sample, encompassing the entire population as the study sample. Data collection was conducted using the documentation method, extracting information from the financial reports of the companies. The data analysis method employed Panel Data Regression with the assistance of E-views 12 application.